Goals for Higher Education Definitions and Directions - Trivett, David A.; ERIC Clearinghouse on Higher Education; American Association for Higher Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
This review of goals for higher education developed from a request from the National Commission on the Financing of Postsecondary Education for information concerning goals. Major studies of goals are reviewed, beginning with "Higher Education for American Democracy," the report of the Commission on Higher Education. Documents produced by major associations, foundations, and government commissions and committees are included as well as relevant documents from the Carnegie Commission and selected state planning documents. A brief concluding section identifies universal access and increased emphasis on the role of the learner as two pervasive themes related to goal formulation over the past 25 years. (MJM)
Availability: Publications Department, American Association for Higher Education, 1 Dupont Circle, Suite 780, Washington, D.C. 20036 ($2.00).
Sponsoring Agency: National Inst. of Education (DHEW), Washington, DC.
Educational level discussed: Higher Education.
Educational level discussed: Postsecondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Needs; Educational Objectives; Equal Education; Higher Education; Institutional Role; Literature Reviews; Postsecondary Education; Student Role